Speed Control of a Single Taipei Mass Rapid Transit System Train by Using a Single Input Fuzzy Logic Controller - Hari Maghfiroh; Oyas Wahyunggoro; Adha Imam Cahyadi; Kuo Lung Lian; Bwo Ren Ke (Institute of Advanced Engineering and Science, 2016)
The purpose of this study was to design a speed controller for mass rapid transit (MRT) train by using a single input fuzzy logic controller (SIFLC). A complete train model, which was designed according to the design of a Taipei MRT train was used for analyzing both mechanical and electrical parts. The SIFLC was used for improving a fuzzy logic controller (FLC) by reducing its number of control rules. The results indicated that the SIFLC exhibited more favorable performance than the FLC did and a substantial reduction in the number of fuzzy rules and processing time. Therefore, tuning the SIFLC was easier compared with tuning the FLC; furthermore, the simulation time of the SIFLC was shorter than that of the FLC, exhibiting reductions of up to 17.3% in a constant track (track without gradient and curvature) and up to 12.27% in a variable track (track with gradient and curvature).